13th International Conference on Ubiquitous Computing and Ambient ‪Intelligence UCAmI 2019‬ 2019
DOI: 10.3390/proceedings2019031040
|View full text |Cite
|
Sign up to set email alerts
|

CLASSY: A Conversational Aware Suggestion System

Abstract: Over the last few years, pervasive systems have seen some interesting development. Nevertheless, human–human interaction can also take advantage of those systems by using their ability to perceive the surrounding environment. In this work, we have developed a pervasive system – named CLASSY – that is aware of the conversational context and suggests documents potentially useful to the users based on an Information Retrieval system, and proposed a new scoring approach that uses semantics and distance based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is a prevalent pattern that is found in around 5-9% of all customer care conversations in multiple domains that we have reviewed. To identify such documents, the agents manually extract the keywords from the conversation and search over their customer service knowledge base (Habibi and Popescu-Belis, 2015;Ferreira et al, 2019). Table 1 shows a conversation where the agent provides a URL 2 to the user.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a prevalent pattern that is found in around 5-9% of all customer care conversations in multiple domains that we have reviewed. To identify such documents, the agents manually extract the keywords from the conversation and search over their customer service knowledge base (Habibi and Popescu-Belis, 2015;Ferreira et al, 2019). Table 1 shows a conversation where the agent provides a URL 2 to the user.…”
Section: Introductionmentioning
confidence: 99%
“…Habibi and Popescu-Belis (2015) proposed a document recommender system by extracting keywords from a conversation using topic modeling techniques. Ferreira et al (2019) have used a similar keyword extraction framework and reported their results on a proprietary dataset.…”
Section: Introductionmentioning
confidence: 99%